"That smooth-faced gentleman … Commodity": Shakespeare's critique of exchange-value in King John. (2nd January 2017) - Smith, Christian A.
Abstract : The word "commodity" in the Bastard's speech in King John 2.1 is listed in the O.E.D . as an example of definition 2b, "expediency". Most of the major scholarly editions of the play also ascribe that meaning to the word. There is historical near-consensus among editors that the Bastard means expediency or self-interest when he says "commodity". Karl Marx quotes these lines in an 1857 newspaper article in such a way that suggests that he reads the word "commodity" as denoting an article with exchange-value. A close reading of the Bastard's speech, an exploration of Shakespeare's use of the word in other plays and a survey of other early modern texts that use the word "commodity" provide evidence that Shakespeare means to denote the more modern economic sense of the word. If this is accepted, then the O.E.D . and future textual practice should be revised to incorporate this change. This also opens a space for King John to be read as a critique of the alienating effects of the newly emerging economic system in the early modern period – capitalism.